Comparison of the Boston Bowel Preparation Scale with an Auditable Application of the US Multi-Society Task Force Guidelines. Issue 2 (29th June 2018) - Heron, Valérie; Martel, Myriam; Bessissow, Talat; Chen, Yen-I; Désilets, Etienne; Dube, Catherine; Lu, Yidan; Menard, Charles; McNabb-Baltar, Julia; Parmar, Robin; Rostom, Alaa; Barkun, Alan N
Abstract: Background: Existing bowel preparation scales (BPS) only modestly predict interval to next colonoscopy. The US Multi-Society Task Force (MSTF) recommends repeating colonoscopies within the year if the preparation does not allow detection of polyps over 5 mm. Aim: This study aims to assess reliability and validity of an auditable application of the MSTF compared with the Boston BPS (BBPS). Methods: We compared an auditable application of MSTF guidelines termed the Montreal BPS (MBPS) with the BBPS using a total cut-off score ≥6 with each segment score ≥2 (BBPS2-6). In sensitivity analyses, we applied the MBPS using a cut-off of 3 mm rather than 5 mm and also assessed the BBPS using an adequacy threshold of total score ≥5 (BBPS5). Videos of 83 colonoscopies (eight for intra-rater agreements) were independently evaluated by nine physicians. Weighted kappas quantified intra- and inter-rater agreements. Associations between scores and clinical outcomes were assessed. Results: The BBPS2-6 and 5 mm MBPS showed moderate to substantial intra-rater agreements (κ=0.44 to 0.63 and κ=0.50 to 0.53, respectively); inter-rater agreements were only fair to moderate and slight to moderate (κ=0.25 to 0.48 and κ=0.19 to 0.50, respectively). Similar results were noted using alternate thresholds of BBPS5 and 3 mm MBPS. No significant associations were found between scores and clinical outcomes. Conclusion: For all scales, intra-rater kappas were superior to inter-rater values, the latter reflecting at best moderate agreement. This modest performance may reflect the dichotomized interpretation of the scales (adequate versus inadequate), differing from previous publications assessing scores as continuous variables. Further studies are required to optimally interpret bowel preparation scales with regard to interval to next colonoscopy.